Pre-service and in-service English teachers’ outlook in the use of online learning - Nasrullah Nasrullah (Universitas Ahmad Dahlan)
The advancement of technology by the emergence of various websites and applications in learning English is inevitably becoming phenomena today. However, many educators especially in-service teachers in Asian secondary schools are reluctant to embody them in the process of English Language Teaching (ELT) since this problem has existed in last decade in the English speaking countries which place English as first and second language; one emerging factor might likely be the status of either x-generations or millennial generation attached to some of them in coin with digital native or digital immigrant as proposed by Marc Prensky. Therefore, this paper is supposed to explain an investigation on the view shown by both sides (pre-service and in-service English teacher). In doing so, a qualitative approach is conducted by involving five pre-service teachers and five in-service teachers in South Kalimantan. The expected finding of this research could depict the variety of chosen views towards the insight and knowledge of ELT resources whether it can be useful for the process of pedagogy in the learning process as well as their classroom instruction.